Correction to: Gender difference in acquired seizure susceptibility in adult rats after early complex febrile seizures - Dai, Yun-Jian; Xu, Zheng-Hao; Feng, Bo; Xu, Ceng-Lin; Zhao, Hua-Wei; Wu, Deng-Chang; Hu, Wei-Wei; Chen, Zhong (Neuroscience bulletin, 2018)
In the original publication of the article, the representative EEG of female rat pups with FS in Figure 1 C and D was incorrectly intercepted from that of male rat pups. This correction does not affect the conclusions of the paper. Figure 1 has been corrected on the online PDF version and displayed below.